2016
DOI: 10.1186/s12889-016-3859-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal polyparasitism with special emphasis to soil-transmitted helminths among residents around Gilgel Gibe Dam, Southwest Ethiopia: a community based survey

Abstract: BackgroundOne third of the world population is estimated to be infected with intestinal parasites. The most affected people are children and the poor people living in tropics and subtropics. Polyparasitism (the concurrent infection with multiple intestinal parasite species) is found to be the norm among the same population although accurate estimate of its magnitude is unknown. It was found that polyparasitism might have a greater impact on morbidity than single species infection which might also increase susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
13
7
Order By: Relevance
“…The overall prevalence of helminths infection found in the present study (18.4%) was relatively lower than reported from other parts of Ethiopia by [ 11 14 ]. Besides, Afework Bitew A, et al [ 15 ] was also reported higher overall prevalence (65.6%) of helminth infection than in the present study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The overall prevalence of helminths infection found in the present study (18.4%) was relatively lower than reported from other parts of Ethiopia by [ 11 14 ]. Besides, Afework Bitew A, et al [ 15 ] was also reported higher overall prevalence (65.6%) of helminth infection than in the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…In the present study, A. lumbricoides (7.8%) was found to be the pre dominant STHs, this is related with many studies [ 2 , 18 , 25 – 27 ], followed by Hookworm (2.8%) and T. trichiura (2.2%). The prevalence of Hookworm infection was comparatively lower than the prevalence of Hookworm infection previously reported from other regions of Ethiopia [ 13 , 16 ], and also lower than the prevalence reported from Langano area [ 11 ]. The prevalence of A. lumbricoides and T. trichiura infections observed in the present study was 7.8% and 2.2%, respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…Data of the STH prevalence from SAC-based surveys in Amhara region in recent years, showed a prevalence ranging from 36.4% [22], up to 66.4% [23]; only a small percentage of children had high intensity infections, as found in the population from the current study. A study conducted in the southwestern part of the country, in an area of similar altitude and at community level, showed an STH prevalence of 52.1%, including infections with both protozoans and helminths [24]. Again the majority of STH infections were categorized as light; the distribution of hookworm by age was similar to that found in the current study.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 84%
“…e revealed finding in this study was higher compared to Gilgel Gibe, Ethiopia [28]. However, light infection is not associated with morbidity; polyparasitism among the community may lead to some conditions like anemia [29].…”
Section: Discussionmentioning
confidence: 46%